ANÁLISE PRELIMINAR DAS CARACTERÍSTICAS AMBIENTAIS EM ESPAÇO DE LAZER: PISTA DE CAMINHADA DA UFMT - Luz, Vanessa de Souza; Maciel, Carolina de Rezende; Pinto Júnior, Osvaldo Borges; Nogueira, Marta Crista de Jesus Albuquerque; Nogueira, José de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707709 The city of Cuiabá, capital of Mato Grosso, has a rigorous climate almost all year round,and its urban structure resulting from uncontrolled and unplanned growth aggravates thissituation. Nowadays, much of the population believes that the only solution to reducing thermaldiscomfort of the city is the air-conditioning indoors, while outdoor environmental comfort is inthe background, almost nonexistent, since the green areas are gradually removed and the soilproofed "for growth" of the city. There are few green areas aimed at leisure in Cuiabá. In thisscenario, the hiking trail from the Federal University of Mato Grosso appears as a demonstrationthat the built and natural spaces can be reconciled harmoniously amid the densely urbanizedareas. In this walking track can be found people from different neighborhoods in Cuiabá / MT aswell as university students, and the times of highest use are early in the morning (06h to 08h) andlate afternoon (17h to 19h), more often on weekends.The objective of this research is thecharacterization of the site regarding land use, vegetation and climate, and then perform analysison the impact of these characteristics on the thermal comfort of the users. For this study pointswere marked every 100 meters, totaling 22 points of data collection, the route of more use byusers, where data were collected on temperature, humidity and surface temperatures. Theschedule of collection was set to 07h and 17h (local time with the greatest number of people). Theroute begins at Avenida Fernando Correa da Costa to the football field at the Federal University ofMato Grosso returning to the starting point, completing a journey of about two kilometers. Thesestudies see developing in the summer period (late 2011 and early 2012) and autumn, and the datacollected during November, December and March. The results of this research will analyze theinfluence of vegetation on local climate mitigation as well as the comfort provided to users.